REFORMULASI KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PERDAGANGAN ORANG SEBAGAI KEJAHATAN LUAR BIASA (EXTRAORDINARY CRIME) - Alfiandi Wisudawansyah Nasution; Asri Vivi Yanti Sinurat (Smart Education, 2026)
The Crime of Human Trafficking is a transnational crime that violates human rights through various forms of exploitation, including sexual exploitation, forced labor, and modern slavery. Although Indonesia has enacted Law Number 21 of 2007 on the Eradication of Human Trafficking, its enforcement still faces numerous challenges, including weak supervision, inadequate victim protection, and the emergence of digital-based trafficking methods. This study aims to analyze the weaknesses of the existing criminal law policy and to formulate a reformed legal policy by positioning human trafficking as an extraordinary crime. Using a normative legal research method, the findings indicate that human trafficking possesses the characteristics of an organized, transnational, and profit-driven crime, thereby requiring special legal treatment. Therefore, it is necessary to strengthen criminal sanctions, optimize asset confiscation, expand corporate criminal liability, and enhance victim protection and recovery mechanisms in order to achieve a more effective and just eradication of human trafficking.